Frequent mutation of K-RAS in addition to BRAF V600E in Ameloblastoma – An immunohistochemical study - Aishwariya Mohanty; Abikshyeet Panda; Pallavi Mishra; Lipsa Bhuyan; Harish Kumar (Oral Oncology Reports)
Background: Ameloblastoma is the most frequently encountered, enigmatic odontogenic tumor whose etiopathogenesis is still controversial. Understanding the pathogenic mechanism involved in Ameloblastoma and its proliferation aids in determining the best treatment option at an early stage. MAPK pathway are known to be active during tooth development, and also mutations in MAPK components have been identified in both benign and malignant tumors. The aim of this study was to evaluate the Immunohistochemical expression of biomarker BRAF V600E and K-RAS in Ameloblastoma and to examine if any, correlation exists between BRAF V600E and K-RAS expression. Methods: 30 formalin-fixed paraffin-embedded blocks of histopathologically diagnosed cases of Ameloblastoma were taken as samples. Immunohistochemistry using K-RAS and BRAF V600E antibody was performed and slides were evaluated both quantitatively and qualitatively using a quick score by an independent observer. Results: K-RAS and BRAF V600E immunoexpression was evaluated and there is a significantly higher expression of K-RAS (mean score 6.20 ± 1.883) when compared with BRAF V600E (mean score 4.50 ± 2.271). BRAF V600E and K-RAS act independently in the pathogenesis of Ameloblastoma as the pattern of variation of BRAF V600E score was uneven when compared to K-RAS values. Conclusion: Our data provide evidence that two independent mutation occurs in the same molecular pathway driving Ameloblastomas. But there is no correlation between K-RAS and BRAF V600E expression. Hence, combination therapy of K-RAS and BRAF V600E inhibitors can be helpful for the treatment of Ameloblastoma.